A Comparative Analysis of the Institutionalization of Citizen Participation in Public-Private Mechanisms for Ensuring Public Safety: Regional Approaches and Their Adaptability within the Decentralized System of Law and Order in the United States - Urazbaev Abatbay Askerbaevich (Periodica Journal, 2024)
The article is devoted to the analysis of public-private partnerships in ensuring public safety in the United States, with an emphasis on the comparative study of models of civic participation. The author explores various approaches to involving citizens in law enforcement, considering their evolution and effectiveness in the context of a decentralized U.S. government system. The article provides a comparative analysis of models of civic participation, taking into account the characteristics of different regions, with an emphasis on their organizational characteristics, training, powers and contribution to ensuring public order. The work highlights the importance of flexibility and adaptability in approaches to organizing volunteer activities in law enforcement agencies.
Keywords: public safety; public order; volunteer